Derivational and Inflectional Morphemes in Songlyrics of Lewis Capaldi - Yastanti, Unpris; Lestari, Indri Diah; Rohati, Titi Dewi (Center of Language and Cultural Studies [CLCS], 2021)
The aim of this study is to identify derivational and inflectional morphemes in song lyrics of Lewis Capaldi. Specifically, the purpose of this research is to know the affixation process in the song lyrics, to classify derivational and inflectional morphemes, and to know the most dominant between derivational and inflectional morphemes in the song lyrics of Lewis Capaldi. The method of this research used descriptive qualitative. The object of this research was taken from the song lyrics of Lewis Capaldi’s album Divinely Uninspired to a Hellish Extent as the first album. The result of this research shows: (1) there are 42 words suffixes such as -ing, -ed, -s, -ness, -able, -ly and one-word prefix re- (2) There are 29 inflectional morphemes and 67,44% while derivational morpheme occurs 14 times and 32,56%, it means inflectional morpheme is the most dominant than derivational morpheme.